Effect of Supplementing Area Specific Mineral Mixture on Productive Performance of Crossbred Cows - Sahoo, Biswanath; Kumar, Ripusudan; Garg, A. K.; Mohanta, Ranjan K.; Agarwal, Anjuli; Sharma, A. K. (Indian Journal of Animal Nutrition, 2017)
The study examined the efficacy of supplementing area specific mineral mixture on nutrient utilization and productive performance of lactating crossbred cows. Twenty lactating cows with average lactation yield of 2100 L and average days after calving of 95 were selected from the local dairy farms in village Lohali, Majhera in the vicinity of mid hills of Uttarakhand state and randomly divided into two groups of 10 each (T1- control;T2-experimental). The area specific mineral mixture (@ 2% of concentrate mixture) was supplemented in T2 group while the roughage source for animals in both the groups was oak tree leaves. The concentrate and roughage ratio was maintained at about 40: 60 level. A digestibility trial of six days duration was conducted at the end of experimental feeding i.e. 90 days. DM intake, milk yield and milk composition were recorded at fortnightly intervals. Average daily DM intake (kg/d) was not influenced by mineral mixture supplementation with values of 11.40 and 12.16 in control and treatment group, respectively. Nutrient digestibility of CP, EE and NDF was higher (P<0.05) in area specific mineral mixture supplemented animals than control group.Supplementation of area specific mineral mixture improved the mineral status of the animals as reflected in improved serum minerals level. The milk yield increased by 9.5% and FCM yield by 11.8%. It was concluded that dietary supplementation of area specific mineral developed for hills of Uttarakhand improved nutrient utilization, mineral bioavailability and milk production performance in dairy cows fed oak leaves based diet.